Pelos trilhos da memória : Alina Paim e o realismo socialista em A hora próxima - Menezes, Fabiana Lisboa Ramos (2016)
This paper proposes a literary analysis of the novel A Hora Próxima, by Alina Paim, it´s try to recognize the marks of socialist realism, a cultural project led by the Communist Political Party of Brazil (PCB) in the years 1940 and 1950. In addition to the partisan press, literature played an important role in this project and the novel can be considered paradigmatic of the proposal. The fictional reconstruction of the railway strike was made through a real research by Alina Paim , that had troubles to this author and revealed the context of the Cold War in Brazil with the persecution of communist intellectuals. The streams of memory, we seek to reveal the relationship between memory, history and literature, discussing the limits and possibilities between history and fiction through the characters of Paim´s romance, which summarize the certainties and illusions of the cultural project of socialist realism in Brazilian literature.